1984
DOI: 10.1111/j.1365-2125.1984.tb02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of (+)‐, (‐)‐ and (+/‐)‐verapamil after intravenous administration.

Abstract: The pharmacokinetics of (+)‐, (‐)‐, and (+/‐)‐verapamil were studied in five healthy volunteers following i.v. administration of the drugs. Pronounced differences of the various pharmacokinetic parameters were observed between the (‐)‐ and (+)‐isomers. The values for CL, V, Vz, and Vss of the (‐)‐isomer were substantially higher as compared to the (+)‐isomer, whereas terminal t 1/ 2Z was nearly identical for both isomers. No dose dependency of the pharmacokinetics could be observed in two subjects who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(63 citation statements)
references
References 21 publications
6
55
1
1
Order By: Relevance
“…In humans two to three times higher verapamil plasma levels are necessary after oral intake in order to cause equieffective increases in P-R intervals of electrocardiograms as after intravenous administration (Eichelbaum et al, 1980). The cause of this difference is that the bioavailability of (-)-verapamil is smaller than that of( + )-verapamil (Eichelbaum et al, 1984) (Eichelbaum et al, 1984) and also because of a higher clearance of (-)-verapamil through the liver (Eichelbaum et al, 1981) the bioavailability of (+ )-verapamil is at least twice that of (-)-verapamil. Thus, it seems reasonable to conclude that at least 25% of the myocardial effects of orally administered racemic verapamil can be accounted for by the (+ )-enantiomer in man.…”
Section: Discussionmentioning
confidence: 96%
“…In humans two to three times higher verapamil plasma levels are necessary after oral intake in order to cause equieffective increases in P-R intervals of electrocardiograms as after intravenous administration (Eichelbaum et al, 1980). The cause of this difference is that the bioavailability of (-)-verapamil is smaller than that of( + )-verapamil (Eichelbaum et al, 1984) (Eichelbaum et al, 1984) and also because of a higher clearance of (-)-verapamil through the liver (Eichelbaum et al, 1981) the bioavailability of (+ )-verapamil is at least twice that of (-)-verapamil. Thus, it seems reasonable to conclude that at least 25% of the myocardial effects of orally administered racemic verapamil can be accounted for by the (+ )-enantiomer in man.…”
Section: Discussionmentioning
confidence: 96%
“…There Eichelbaum et al, 1980Eichelbaum et al, , 1981Eichelbaum et al, a,b, 1984McAllister & Kirsten 1982). Previous studies have demonstrated that the same concentration of plasma verapamil following oral administration appeared to be two to three times less potent than that following i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Verapamil was recently found to exhibit stereoselective plasma protein binding and hepatic metabolism in humans (Eichelbaum et al, 1984;Vogelgesang et al, 1984;Echizen et al, 1985). If the same phenomena occur in rats there is a possibility that calcium antagonist potency ratios in vivo and in vitro may be different.…”
Section: Introductionmentioning
confidence: 99%